Analisis Bibliometrik Penerapan Metode Pembelajaran Jigsaw untuk Meningkatkan Keterampilan Komunikasi Siswa pada Tahun 2017-2021 - Anggraini, Isti Nur; Mahdiannur, Muhamad Arif (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2023)
Bibliometric analysis is a set of mathematical and statistical methods used to analyze and measure the quantity and quality of books, articles, and forms of publication. This article is a bibliometric analysis that uses PoP indexed journals on Jigsaw and Communication Skills with the help of software to analyze data, namely VOSviewer. The purpose of this study is to determine the development of research related to Jigsaw and Communication Skills in terms of the distribution of bibliometric maps and trends of research or publication on the PoP database using VOSviewer software. In particular, this article discusses the development of citations, publication trends, author collaborations, titles, keywords, abstracts, and country statistics with the topic of Jigsaw and Communication Skills in the 2017-2021 period. The keywords used in searches on PoP software are